Effect of rice bran rancidity on the emulsion stability of rice bran protein and structural characteristics of interface protein. (December 2021) - Li, Helin; Li, Fang; Wu, Xiaojuan; Wu, Wei
Abstract: Rice bran protein (RBP) was prepared from rice bran (RB) under different storage periods (0, 1, 5, 7, 10 d), and isolated RBP was used to prepare protein emulsion. The RB crude oil acid value, the RBP oxidation degree, the RBP emulsion stability, and the interface-adsorbed protein and interface-unabsorbed protein structure of RBP emulsion were evaluated. With the RB storage time prolonged, the acid value of RB crude oil and the RBP carbonyl content gradually increased, indicated the occurrence of RB rancidity and RBP oxidation. Furthermore, RBP oxidation led to significant changes in the RBP emulsion stability. Moderate oxidation (RB stored for 1 d) could increase the stability of RBP emulsion, while excessive oxidation (RB stored for 5–10 d) could weaken the emulsion stability. In addition, the increasing RB storage time changed the flexibility and aggregation degree of the adsorbed protein and unabsorbed protein on the emulsion interface. The correlation analysis showed that the stability of the protein emulsion was highly correlated ( P < 0.01) with the flexibility of interface-adsorbed protein, but showed little correlation with the flexibility of the unabsorbed protein at the interface. By regulating the oxidation degree of RPB to improve the emulsion stability, this research can provide a theoretical reference for promoting the stability of protein emulsions, and enlarging their applications in food systems. Graphical abstract: Image 1 Highlights: The oxidation of RBP induced by the rancidity of RB changes the emulsion stability. Oxidation of RBP changes the structure of emulsion interface protein. The flexibility of interface-adsorbed proteins determines the emulsion stability.